1077. In Vitro Activity of Delafloxacin Agent Against Bacterial Isolates Recovered from Patients with Cancer. (4th December 2021) - Gerges, Bahgat; Raad, Issam I; Rosenblatt, Joel; Shelbume, Samuel; Prince, Randal; Rolston, Kenneth
Abstract: Background: Fluoroquinolones have been used for infection prevention in patients with cancer (PWC). They are active against many Gram-negative bacilli (GNB) but are less active against Gram-positive organisms (GPO). Quinolone resistance is increasing and many institutions are using combination regimens for antimicrobial prophylaxis. We evaluated the in vitro activity of delafloxacin (DLX), a novel fluoroquinolone, and selected comparators against 560 bacterial isolates from PWC. Methods: Isolates were from recent blood cultures. Susceptibility testing and time kill studies (TKS) were performed using CLSI approved methodology. Appropriate ATCC control strains were used. We calculated MIC50, MIC90, MIC ranges and percent susceptibility using FDA breakpoints when available. TKS were performed on 4 streptococcus mitis isolates at concentrations of MIC, 4x MIC, and 8x MIC. Results: DLX was more active than ciprofloxacin (CIP) and levofloxacin (LEV) against methicillin-susceptible (MSSA), and resistant (MRSA) S. aureus, coagulase-negative staphylococci (CoNS), and viridans group streptococci (VGS), and had similar activity against beta-hemolytic streptococci . It also had low MICs for Bacillus species (SPP.), Listeria monocytogenes, Micrococcus spp ., and Rothia spp. Overall GPO susceptibility was 73% to DLX, 42% to CIP, and 52% to LEV. The activity of DLX against Enterobacterales was similar to CIP and LEV. All 3 agents had moderate activity against Citrobacter spp ., and non-MDR P. aeruginosa . Notably, all 3 quinolones had poor activity against E. coli, P. mirabilis, and MDR P. aeruginosa, all common pathogens in PWC. All 3 had low MICs for Acinetobacter spp. DLX and LEV achieved peak bactericidal activity at 6-8 h against all 4 VGS isolates (maximum activity at 8x MIC) but this was not always sustained at 24 h. Table 1. Percent Susceptibility of selected Gram-positive isolates to Delafloxacin, Ciprofloxacin and Levofloxacin Table 2. Percent Susceptibility of selected Gram-negative isolates to Delafloxacin, Ciprofloxacin and Levofloxacin Figure 1. Bactericidal Activity of DLX at 1x, 4x, and 8x MIC against VGS - Time Kill Study Conclusion: DLX is more active than CIP and LEV against many GPO from PWC (including S. aureus and VGS), but like these agents there are significant gaps in its coverage against GNB. It is probably not suitable as a single agent for antimicrobial prophylaxis in high-risk PWC. The current practice of combining a quinolone with a beta-lactam probably still represents the best option in PWC who need prophylaxis. Disclosures: Kenneth Rolston, MD, Tetraphase Pharmaceuticals (Grant/Research Support)